Off-shell Nucleons in Intermediate Energy Physics - Poulis, G. I. (HNPS Advances in Nuclear Physics, 2020)
I discuss some issues pertaining to vertices involving virtual (i.e. off-mass-shell) nucleons, namely, in which processes off-shell vertices appear, their transformation properties under field redefinitions, and the attempts that have been made to esti- mate their effects in electromagnetic processes at intermediate energies.